The Effect of Economic Growth and Population on the Unemployment Rate in Gowa Regency - Asdar, Asdar; Akhmad, Akhmad; Jam’an, Andi; Mustari, Nur Annisa (Perpustakaan dan Penerbitan Unismuh Makassar, 2023)
This study aims to determine Economic Growth, and the Minimum Wage affects the Unemployment Rate in Gowa Regency. data collection technique uses secondary data sourced from the Central Statistics Agency of Gowa Regency. The data analysis techniques used are classical assumption test, multiple linear regression analysis, coefficient of determination (R), simultaneous test (f test) and partial test (t test). The results showed that based on the results of regression analysis and partial tests (t test) the variables economic growth and population had a significant negative effect on the Unemployment Rate in Gowa Regency and the magnitude of the correlation value obtained by the coefficient of determination (R Square) output of 0.684 which implies that the effect of the free variables of Economist Growth and Population Numbers on the variables bound by the Unemployment Rate in Gowa District is 68.4%.